Efektivitas Pembelajaran Pendidikan Agama Islam Dalam Jaringan Masa Pandemi Covid-19 di SMKN 1 Al-Mubarkeya - Rahma Sarah; Misnawati Misnawati; Sri Mawaddah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study uses a descriptive quantitative approach, with data collection methods using questionnaires and documentation. The selection of samples using the Probability Sampling technique with the simple random sampling method from class X, XI and XII. The research was carried out by distributing questionnaires made with Google Forms and then sharing them online via Whatsap. Data analysis used quantitative descriptive analysis. The results of the student's research stated that online learning was still not effective based on data acquisition from 25 statements given by researchers to 97 respondents. It can be seen from the average results on the indicators of learning effectiveness. First, active learning obtains an average value of 2.62 belonging to the less effective category. Second, various learning methods obtain an average value of 3.09 belonging to the less effective category. Third, learning motivation obtains an average value of 2,826 belonging to the less effective category. Fourth, the democratic atmosphere obtained an average value of 2.6 belonging to the less effective category. Fifth, lessons at school need to be linked to real life, obtaining an average score of 2.94 belonging to the less effective category. Sixth, conducive learning interactions obtain an average value of 2.34 belonging to the ineffective category. And seventh, the diagnosis of learning difficulties obtained an average value of 2,746 belonging to the less effective category. Thus, the total average of all indicators obtained a value of 2.7374 belongs to the less effective category. So that learning Islamic Religious Education online during the Covid-19 pandemic at SMKN 1 Al-Mubarkeya Ingin Jaya Aceh Besar was declared less effective.